(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
The stock market is a complex phenomena that can be influenced by a myriad of factors. However, gross domestic product and inflation rate are considered two most critical variables affecting the stock market’s performance. This research aims to investigate the impact of GDP and inflation on the volatility of stock exchange performance of Nepal and Sri Lanka by employing the Least Square Regression Approach. Both countries are situated in South Asia and boast agrarian-based economies. Additionally, they are renowned for their rich cultural heritage, ancient civilizations, and historical sites. As a result, this research is centred on investigating the unique aspects of these two nations. Time series data of closing stock of every fiscal year from 1997 to 2021 was collected from authentic online sources and analyzed with the help SPSS Version 20. The findings of this study indicate a significant influence of GDP and inflation on stock index of both countries (p-value < 0.05). The analysis further indicates that the microeconomic variables accounted for 78.7% and 91.9% of the stock index variation for Nepal and Sri Lanka, respectively. Furthermore, the study finds a strong positive correlation between GDP and stock index of both countries, while inflation exhibits a weak negative correlation with the NEPSE index and a moderate negative correlation with the CSE index. Despite the focus on only two independent macroeconomic variables, this research highlights their significant impact on stock market performance. Policymakers and investors can leverage these findings to make informed decisions while navigating the complexities of the stock market.